2023
DOI: 10.1007/s11033-022-08211-5
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of low dose ionizing radiation against cancer, dementia, and diabetes: evidences from epidemiological, clinical, and preclinical studies

Abstract: The growing use of ionizing radiation (IR)-based diagnostic and treatment methods has been linked to increasing chronic diseases among patients and healthcare professionals. However, multiple factors such as IR dose, dose-rate, and duration of exposure influence the IR-induced chronic effects. The predicted links between low-dose ionizing radiation (LDIR) and health risks are controversial due to the non-availability of direct human studies. The studies pertaining to LDIR effects have importance in public heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Studies on noncancer effects that occur years or decades after radiation exposure are very important not only in the field of radiation protection (where lifetime risk matters), but also in medicine (particularly after radiotherapy): given that the dose threshold for noncancer effects generally decreases with increasing post-irradiation time, the longer the post-radiotherapeutic survival of patients, the broader the spectrum of normal tissue complications of concern (196). Such viewpoints would be needed to consider whether clinical benefits outweigh risks of normal tissue complications (DCS and other life-threatening noncancer diseases as well as secondary cancer) after radiotherapy, e.g., in considering justification of radiotherapy for noncancer diseases, such as coronavirus disease 2019 (COVID-19) pneumonia (197)(198)(199)(200)(201)(202), refractory ventricular tachycardia (192,193), dementia and Alzheimer's disease (203)(204)(205). This section considers late occurring noncancer effects on the radar other than those on the eye and the circulatory system.…”
Section: Other Late-occurring Noncancer Effects On the Radarmentioning
confidence: 99%
“…Studies on noncancer effects that occur years or decades after radiation exposure are very important not only in the field of radiation protection (where lifetime risk matters), but also in medicine (particularly after radiotherapy): given that the dose threshold for noncancer effects generally decreases with increasing post-irradiation time, the longer the post-radiotherapeutic survival of patients, the broader the spectrum of normal tissue complications of concern (196). Such viewpoints would be needed to consider whether clinical benefits outweigh risks of normal tissue complications (DCS and other life-threatening noncancer diseases as well as secondary cancer) after radiotherapy, e.g., in considering justification of radiotherapy for noncancer diseases, such as coronavirus disease 2019 (COVID-19) pneumonia (197)(198)(199)(200)(201)(202), refractory ventricular tachycardia (192,193), dementia and Alzheimer's disease (203)(204)(205). This section considers late occurring noncancer effects on the radar other than those on the eye and the circulatory system.…”
Section: Other Late-occurring Noncancer Effects On the Radarmentioning
confidence: 99%
“…Ionizing radiation is used to treat cancer [ 1 , 2 ], but is also a carcinogen [ 3 , 4 ]. Alongside that, there has been mounting interest not only in radiotherapy for non-cancer diseases [ 5 , 6 , 7 , 8 , 9 ], but also the non-cancer effects of radiation exposure that occur at doses or dose rates much lower than previously suggested or considered [ 9 , 10 , 11 ]. This underlines the need to consider both the cancer and non-cancer effects of medical (diagnostic or therapeutic), occupational or environmental exposure to radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous authors have demonstrated that low-dose radiation (LDR) has the potential to increase the response to anticancer medications and decrease side effects by enhancing various phenomena, such as adaptive response and cell-cell communication (Chandna et al, 2002;Liu et al, 2004 andPaithankar et al, 2023). Additionally, response of the immune system (Hosoi & Sakamoto, 1993) and inhibition of metastasis subsequently have been observed with LDR (Liu, 2007).…”
Section: Introductionmentioning
confidence: 99%